Inflammatory and neurodegenerative serum protein biomarkers increase sensitivity to detect clinical and radiographic disease activity in multiple sclerosis - Chitnis, Tanuja; Qureshi, Ferhan; Gehman, Victor M.; Becich, Michael; Bove, Riley; Cree, Bruce A. C.; Gomez, Refujia; Hauser, Stephen L.; Henry, Roland G.; Katrib, Amal; Lokhande, Hrishikesh; Paul, Anu; et al. (Nature communications, 2024)
The multifaceted nature of multiple sclerosis requires quantitative biomarkers that can provide insights related to diverse physiological pathways. To this end, proteomic analysis of deeply-phenotyped serum samples, biological pathway modeling, and network analysis were performed to elucidate inflammatory and neurodegenerative processes, identifying sensitive biomarkers of multiple sclerosis disease activity. Here, we evaluated the concentrations of > 1400 serum proteins in 630 samples from three multiple sclerosis cohorts for association with clinical and radiographic new disease activity. Twenty proteins were associated with increased clinical and radiographic multiple sclerosis disease activity for inclusion in a custom assay panel. Serum neurofilament light chain showed the strongest univariate correlation with gadolinium lesion activity, clinical relapse status, and annualized relapse rate. Multivariate modeling outperformed univariate for all endpoints. A comprehensive biomarker panel including the twenty proteins identified in this study could serve to characterize disease activity for a patient with multiple sclerosis. Inflammatory and degenerative processes are thought to play a role in the pathophysiology of multiple sclerosis. Here, the authors identified twenty serum proteins associated with increased clinical and radiographic disease activity.